STRATEGI KOMUNIKASI PARIWISATA MAKAM TUA RAJA SIDABUTAR SEBAGAI CITRA AMBARITA - Edward Gilbert Munthe; Helen Sitorus (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This research is motivated by the number of tourist attractions that have recently attracted the public, both local people and immigrants. Marketing communication strategy is an effort made in order to attract interest, provide awareness, or convey to the public about the existence of products or services that are sold and marketed in a location with the aim of people or consumers knowing, buying and then becoming customers. Meanwhile, a tourist spot that is visited by the surrounding community is the Old Tomb Tour of King Sidabutar. This study aims at analysing the existing communication messages from the Old Tomb of King Sidabutar tourism. This study uses a descriptive type of research that is used to find out about the messages in the Old Tomb of King Sidabutar tourism. Researchers also collected data from interviews, observations and documentation. The results of the study indicate that, (1) Marketing communication of the Old King Sidabutar Tomb in increasing visitors (2) Accessibility which aims to make it easier to reach tourist sites of the Old King Sidabutar Tomb through the transportation system (3) Tourism Destinations which explain the historical traditions of the Old King Sidabutar Tomb and some of the existing cultures (4) Resources and tourism institutions that show management from both the community and the government that manages the tour of the Old Tomb of King Sidabutar.